Productivity Increasing using the Automation Machine for Arranging Wheels into the Finished Goods Rack in a Wheels Assembly Manufacturer - Jakkrit Thudthong; Noppadol Maneerat; Chanathip Wongsomboon; Sutikamon Sukasem; Bundit Pasaya; Virot Wuti (My University, 2023)
The automotive parts manufacturing business has continuously increased market competition. The production costs are always discussed when negotiating prices. (The price of the product is often taken into account in always negotiating with customers) Therefore, manufacturers focus on continuously reducing production costs. To maintain reasonable profits in this research, a method to reduce costs by creating an automation system to replace manual labor in the wheel packaging workstation is presented. Because human labor is one of the main costs in the cost of producing goods. This research was carried out in a wheel assembly plant in the TFD Industrial Estate and after the implementation an automation system for wheel arranging. The company can reduce production costs by reducing the number of employees in the workstation packing for 3 people and can reduce production costs by 522,000 baht per year and increase productivity by 127.84% as well.
Keywords: Advanced Manufacturing and Logistics Optimization; Manufacturing Process and Optimization; Industrial Automation and Control Systems